2014
DOI: 10.1093/nar/gku620
|View full text |Cite
|
Sign up to set email alerts
|

The human Piwi protein Hiwi2 associates with tRNA-derived piRNAs in somatic cells

Abstract: The Piwi-piRNA pathway is active in animal germ cells where its functions are required for germ cell maintenance and gamete differentiation. Piwi proteins and piRNAs have been detected outside germline tissue in multiple phyla, but activity of the pathway in mammalian somatic cells has been little explored. In particular, Piwi expression has been observed in cancer cells, but nothing is known about the piRNA partners or the function of the system in these cells. We have surveyed the expression of the three hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 65 publications
7
126
2
Order By: Relevance
“…Because of the similarity of tsRNAs to piRNAs, we hypothesized and then proved that these molecules can interact with Piwi proteins (24). Interestingly, in a recent report, the Tetrahymena Piwi protein Twi12, essential for growth, was found to be loaded with mature tRNA fragments (25).…”
Section: Ts-4521mentioning
confidence: 98%
“…Because of the similarity of tsRNAs to piRNAs, we hypothesized and then proved that these molecules can interact with Piwi proteins (24). Interestingly, in a recent report, the Tetrahymena Piwi protein Twi12, essential for growth, was found to be loaded with mature tRNA fragments (25).…”
Section: Ts-4521mentioning
confidence: 98%
“…piRNAs are highly expressed in reproductive tissues, but are also expressed in the brain [95], and a normal human plasmaderived exosome had 1.31% piRNAs [96]. Some piRNAs can be associated with HIWI2 in somatic cells including cancer cells [97]. Many piRNAs in exponentially growing or growth-arrested human breast cancer MCF-7 cells have also been identified [70].…”
Section: Piwi-interacting Rnas Are Related To Tumorigenesismentioning
confidence: 99%
“…A growing number of studies have found that piwi proteins in humans and mice, specifically, HIWI, PIWIL2 and PIWIL2-like proteins, are expressed in various types of tumor cells. In addition, piRNAs were also detected in these cells [64,90].…”
Section: Piwi-interacting Rnasmentioning
confidence: 86%